Catalytic pyrolysis of brown algae using carbon dioxide and oyster shell. (December 2019) - Choi, Dongho; Nam, In-Hyun; Park, Young-Kwon; Ok, Yong Sik; Lee, Jechan; Kwon, Eilhann E.
Highlights: Using CO2 in pyrolysis of brown algae enhanced the production of gaseous products by 610%. Pyrolysis of brown algae in two-stage pyrolysis setup yielded a negligible amount of pyrolytic oil. Oyster shell effectively provided CO2 in in situ pyrolysis of brown algae in N2 and enhanced CO production by 185%. Ex situ brown algae pyrolysis in CO2 with oyster shell at ≥315 °C produced 670% more CO and 3120% more H2 than in situ pyrolysis. Abstract: In this work, the pyrolysis of brown algae ( Saccharina japonica ( S. japonica )) was investigated to recover energy as a form of syngas (H2 and CO). For this, this work emphasizes the use of CO2 as a pyrolysis medium and oyster shell as a catalytic material in the pyrolysis of S. japonica . Pyrogenic products generated from the catalytic pyrolysis of S. japonica in N2 and CO2 were characterized. In particular, the enhanced generation of CO was substantial at 720 °C. This enhanced generation of CO was most likely because of the enhanced thermal cracking of volatile matter that evolved during the catalytic pyrolysis of S. japonica . The enhanced CO generation was likely catalytically expedited by biogenic salts such as calcite (CaCO3 ) in the oyster shell. The introduced approach for exploiting CO2 in the catalytic pyrolysis could be a more sustainable option to treat algal biomass such as brown algae and develop an effective waste-to-energy strategy.